Utilization of unused spaces a study of corners, nooks and crannies in residential houses - Bringas, Lenore Gayao; Mayo, Adelaida Villaraza (1998.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Space (Architecture)